PENGEMBANGAN E-MODUL MENGGUNAKAN FLIP PDF PROFESIONAL UNTUK MATERI BANGUN RUANG SISI DATAR PADA KELAS VIII DI SMPN 2 KEC. AKABILURU - Siska Elvadiningsih (Departemen Matematika, 2021)
The research aims to develop an e-module on flat-side space material for junior high school students which is valid and practical. This type of research is included in research and development (R&D) using the 4-D model. The 4-D model consists of four stages, namely define, design, develop and disseminate. But this time research is only up o the stage of development. This research was conducted in UPTD SMPN 2 Kec. Akabiluru to students of class VIII.1 and VIII.2. Data obtained in analysis with quantitative and qualitative analysis. Based on validation by experts, the e-module are categorized as valid with a validity level of 85,00%. For the technical response of students at the one-to-one evaluation of class VIII.1 is 87,72% and is categorized practical, and the small-group evaluation of class VIII.2 is 86,00% and is categorized practical. Based on these data it could be concluded that the e-module are worthy to use. Keywords – E-Module, Mathematics, Valid, Practical